In vitro, In vivo Studies and Clinical Studies Provide Significant Results that Facilitate a Scientific Discussion on the Therapeutic Efficacy of Homeopathic Medicines - Tarro, Giulio; De Giorgio, Giovanni (British Journal of Healthcare and Medical Research, 2025)
Homeopathy, founded about two centuries ago by Samuel Hahnemann, is a clinical methodology based on the law of similarity: similia similibus curentur . During homeopathic therapy, small doses of substances are administered to the patient which, if administered to a healthy subject in large doses , would produce symptoms similar to those suffered by the patient. The active ingredients contained in homeopathic medicines are extremely diluted, in fact, in some medicines, the active ingredients are not present at all, therefore homeopathy is often compared to a placebo therapy by numerous skeptics who disapprove and criticize it harshly, but, based on the results obtained with scientific research, many disapprovals and many criticisms can be revised and scaled down significantly, in fact, authoritative in vitro studies, in vivo studies and clinical studies provide very significant information that facilitate a scientific discussion on the effectiveness of homeopathic medicine. If it is true that some homeopathic medicines are totally devoid of active ingredients, it is equally true that they are effective, not because of the placebo effect, but probably because of the so-called water memory . The theory is interesting: the water in which the active ingredients are diluted and homeopathically dynamized would undergo significant modifications, and even when the active ingredients disappear definitively from the aqueous solution through progressive dilutions, the water would retain the memory of them. This theory is now supported by authoritative scientific studies and enlightening experiments on the basis of which it is possible to suppose that the active ingredients, even when they are no longer present in the aqueous solution, remain imprinted in the water's memory . Alongside this supposition it is important to add some certainty: the effects of ultra-diluted homeopathic remedies have been clearly highlighted during some rigorous in vitro experiments. and the results were published in authoritative scientific journals . In vitro experiments, for obvious reasons, they provide information on real, not suggestive effects, in fact microscopists cannot suggest the cells they observe under the microscope and the cells observed microscopically cannot be suggested by the microscopists, in short, in in vitro studies the placebo effect cannot be called into question and The effects caused by homeopathic dilutions and clearly visible under the microscope are obviously attributed to homeopathy, not to suggestion. This is why the effects highlighted in in vitro experiments facilitate the discussion on the concrete facts that are clearly visible under the microscope and on the concrete therapeutic potential of homeopathic medicines, they also facilitate the discussion on the efficacy of homeopathic medicines found in various in vivo experiments and in various clinical studies. Taking into account the authoritative scientific studies that have been carried out up to now, considering the importance of scientific progress, reflecting on the results reported in the authoritative articles examined during our bibliographical research, we believe that scientific research on homeopathy should be encouraged and not discouraged, therefore, with this article we intend to encourage, scale down some commonplaces on homeopathic medicine and address a discussion based on concrete facts , experiments and works carried out in compliance with science.